Double gold activation of 1-ethynyl-2-(phenylethynyl)benzene toward 5-exo-dig and 6-endo-dig cyclization reactions - Villegas-Escobar, Nery; Larsen, Mie Højer; Hashmi, A. Stephen K. (Chemistry - a European journal, 2017)
In this work, a detailed characterization was carried out of the ring-closure mechanism of EPB (1-ethynyl-2-(phenylethynyl)benzene) toward the 5-exo-dig and 6-endo-dig cyclization reactions, catalyzed by two Au-N-heterocyclic carbene (NHC) moieties. It was found that the 5-exo-dig cyclization takes place with a slightly lower activation barrier and larger exothermicity compared to that of the 6-endo-dig cyclization, in agreement with the available experimental data. A phenomenological partition (structural and electronic) for rate constants computed using transition-state theory and the reaction force analysis was used to shed light into the nature of the activation rate constant. It was found that rate constants are influenced by a strong structural component, which is larger for the 5-exo-dig cyclization due to the strain to form the five-membered ring. On the other hand, the gold activation mechanism is evidenced by a σ- and π-coordination of the Au−NHC moieties to the EPB substrate. It was found that differences in the σ-coordination arise on the reaction path for the 5-exo-dig and 6-endo-dig cyclizations. Thus, in the 6-endo-dig cyclization the σ gold-EPB interaction is weakened as a consequence of the formation of the cationic aryl intermediate, while for the 5-exo-dig cyclization this interaction was found to be favored. Furthermore, although minor changes in the Au-EPB coordination occur on the reaction path, these bonds are formally established in the TS vicinity. Results support the concerted nature of the dual gold activation mechanism.